STUDI KASUS MENGURANGI KECEMASAN PADA CALON AKSEPTOR KONTRASEPSI IUD DENGAN TERAPI NON FARMAKOLOGI SLOW DEEP BREATHING - Hertati, Dessy; Stefanicia, Stefanicia; Kasanova, Evy; Natalia, Vita (NHM PRESS, 2025)
The use of intrauterine contraceptive devices (IUD) still faces several obstacles, one of which is the anxiety that arises related to the insertion procedure.This anxiety can affect the decision of potential acceptors in choosing the IUD as a contraceptive method. To reduce the level of anxiety, one technique that can be applied is Slow Deep Breathing, which is a method of breathing done slowly and deeply. The goal is to provide midwifery care to a new IUD contraceptive acceptor, Mrs. Y, P3 A0, 39 years old, at the UPTD Puskesmas Pahandut, Palangka Raya City.The type of research used is qualitative descriptive with a case study approach method. The design uses field observation.The data collection method used was through interviews and analysis of midwifery care documentation. Data analysis is obtained from case study research by creating narratives from observation results and descriptions of midwifery care analysis, assessment, formulating diagnoses, planning, implementing, and conducting evaluations.This research was conducted in August 2024. The result is that Mrs. Y felt calmer and more comfortable after practicing the Slow Deep Breathing technique. The results of this study are expected to help clients who will undergo IUD contraceptive insertion to feel more at ease, achieve peace of mind, and reduce anxiety.